The influence of oxygen partial pressure in the growth atmosphere on the coloration of SrTiO3 single crystal fibers. Issue 30 (23rd June 2016) - Kamutzki, Franz; Guguschev, Christo; Kok, Dirk J.; Bertram, Rainer; Juda, Uta; Uecker, Reinhard
Abstract : The coloration of SrTiO3 single crystal fibers, depending on the oxygen content in the growth atmosphere, was investigated. Abstract : A variety of SrTiO3 (STO) fibers have been grown by the laser-heated pedestal growth method to determine the influence of the oxygen partial pressure in the growth atmosphere and the composition of the feed material on the coloration of SrTiO3 . Crystals grown in oxygen rich environments are typically brown and show high Sr/Ti-ratios. Decreasing oxygen partial pressure leads to less coloration and decreasing Sr/Ti-ratios. Growth under very low oxygen partial pressure produces crystals with blueish and greyish tints. By using a feed rod with Sr-excess in an atmosphere that contains about one vol% oxygen, colorless STO fibers can be produced. The main reason for the low transmittance in crystals grown in high oxygen partial pressures is probably off-stoichiometry and the formation of scattering centers from clustered vacancies. The formation energy of the metal vacancies is considerably higher in oxygen poor environments which hinders the formation of the scattering centers. This phenomenon is further prevented by Sr-excess in the feed material that compensates SrO(g) evaporating from the melt.